Estudo da relação entre a comunidade parasitária, meio ambiente e dinâmica da população de Prochilodus lineatus (Valenciennes, 1836) e Astyanax altiparanae Garutti & Britski, 2000, na planície de inundação do alto rio Paraná, Brasil. - Perez Lizama, Maria de los Angeles (2003)
One hundred and forty-nine fish were collected in the high Paraná river floodplain, Brazil, of these 121 (82.1%) were parasited. Thirty-three species of metazoan parasite specie were recorded. Only Rhinonastes pseudocapsaloideum was classified as secondary, while that the other species were classified like satellites. The metazoan parasite community of P. lineatus show the typical pattern of distribution overdisperse. The pair of species of ectoparasite Ergasilus sp.-Tereancistrum curimba n. sp. showed associated positively, being theirs abundance also positively correlated. Among the endoparasites, the pair Saccocoelioides magnorchis-S. nanii presented positively associated and with the abundance positively correlated. The mean diversity in the infracommunities of P. lineatus was H= 0.6875 ± 0.4398. Regarding the richness of species from the community, had the predominance of 4 species by host. The standard length of the host did not present correlated with the diversity (rs = 0.1726; p = 0.0533). The monogenean T. curimba n. sp. and Kritskya boegeri, and the digenean S. magnorchis and S. nanii presented significant correlation between the standard length and the abundance of parasitism. Correlation between the age of the fish and to prevalence was not observed. The species Amplexibranchius sp, K. boegeri and S. magnorchis presented significant differences in the parasite abundance according to the age class of the hosts. For Amplexibranchius sp., the class more intensely parasited was 3 years. Already for K. boegeri the intermediate age classes 3, 4 and 5 years went the more parasited. Only Tereancistrum curimba n. sp. showed significant difference in the prevalence between hosts male and female where the female presented themselves more parasited. It was not observed significant difference from the abundance of parasitism between the sexes of the hosts.